The Benefits of Revenue Diversification on Bank Profitability and Stability: An Empirical Study on Indonesian Commercial Banks - Setiadi, Robertus; Danarsari, Dwi Nastiti (STIE Malangkucecwara, 2024)
Traditional business activities of commercial banks in Indonesia experienced a shift as indicated by the percentage of non- interest income per interest income from 26.1% in 2014 to 51.3% in 2020. The study aims to determine revenue diversification, internal determinants, and macroeconomic determinants in affecting profitability, stability, while also observing the role of bank capitalization. This study analyze sample of Conventional Commercial Banks in Indonesia from 2013 to 2020, using dynamic panel data GMM. Research proves that direct effect of non-interest income on revenue diversification has a significant positive effect on ROA and risk adjusted ROA, as well as a negative effect on NPL; as the indirect effect of only significantly affects RAROA. However, there are contradictions in the results of research using the interaction variable of revenue diversification with bank capitalization. The empirical test results also prove the role of the control variables cost income ratio, deposit to total asset, bank capital, loan to total asset, bank size, inflation rate, and GDP growth in affecting bank performance and stability. This study proves the specific benefit of revenue diversification for commercial banks in Indonesia as a whole, although it does not apply to BUKU 1 banks.